Perceptions on the use of English as a Lingua Franca at home : multilingual families in Finland and Norway - Gühr, Louisa (2021)
This study investigates the use of English as a lingua franca (ELF) in the context of four multilingual families from two Nordic countries: Finland and Norway. These families make use of ELF in their family interactions. ELF has been extensively researched in different social contexts, and yet, it has been researched surprisingly little in the context of multilingual family interaction (for exceptions, see e.g. Soler & Zabrodskaja, 2017; Pietikäinen, 2017). The aim of this study is to answer to how the research participants see the role of ELF in their family interactions and how, according to them, their use of ELF has changed over time in their family interactions. The data set consists of part of the interview data that was collected during 2018 for the research project “Linguistic Constellations of Lingua Franca Families - A Longitudinal Inquiry into the Development of Multilingual Practices” led by Dr Kaisa S. Pietikäinen. The selected data is made up of four semi-structured inter- views with the parents of four multilingual families that make use of ELF in their family interactions. The data was qualitatively analysed through a thematic-based narrative research method—phenomenography. In the analysis, six phenomena were found: 1. the use of ELF in multilingual families over time; 2. the use of ELF in multilingual family interactions; 3. the use of ELF between parents in multilingual families; 4. ELF as a linguistic support for learning to speak other languages present in the context of multilingual families; 5. ELF as a tool for communicating with extended family members in the context of multilingual families; and 6. ELF as a hindering factor when learning other languages in the context of multilingual families. This study shows that the use of ELF in multilingual families is in constant change and development. The participants do not use ELF in isolation in their family interactions, but rather in a way in which all the languages that the family members share are somewhat intertwined. One could say that ELF used in multilingual families is a language of its own in each of the multilingual families that exist out there and that their use cannot be strictly defined since each family might have a variety of language identities, beliefs and practices that make their use of ELF in their family unique. My findings could serve as a tool to better understand the linguistic and interpersonal realities of multilingual families that use ELF. I hope that this thesis and possible future research will help to shed light on the way in which ELF is present in multilingual families for diverse amount of time and in diversely creative ways.